2006
DOI: 10.1002/cbf.1339
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase gene polymorphisms in Turkish patients with diabetes mellitus

Abstract: Glutathione S-transferases (GSTs) are enzymes involved in the metabolism of many disease-causing electrophilic substrates and protect the cells against oxidative stress. In the present study, we investigated the GSTM1, GSTT1 and GSTP1 gene polymorphisms in diabetic patients and healthy individuals and searched whether polymorphisms in GST genes are associated with diabetes mellitus (DM) in the Turkish population. The study population consisted of 98 unrelated healthy individuals and 98 patients with DM. Genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 19 publications
5
72
0
Order By: Relevance
“…Showed that the GSTP1 heterozygous genotype is significantly (P=0.001) related with T2DM in compared in control .In contrast, Yalin et al (2007) and Oniki et al(2008) found that the polymorphism in GSTP1 may not play an active role in the pathogenesis of disease in the Turkish people and Japanese people respectively. These data could be determent by differences in ethnic groups in the selected groups of study (Delles et al,2008).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Showed that the GSTP1 heterozygous genotype is significantly (P=0.001) related with T2DM in compared in control .In contrast, Yalin et al (2007) and Oniki et al(2008) found that the polymorphism in GSTP1 may not play an active role in the pathogenesis of disease in the Turkish people and Japanese people respectively. These data could be determent by differences in ethnic groups in the selected groups of study (Delles et al,2008).…”
Section: Discussionmentioning
confidence: 92%
“…Diabetes Mellitus Type 2 is disease that develops through an exposure to risk factors in environment and genetic susceptibility There are a common variation force is exerted on beta cells in all patients such force are the abnormal lipids and the toxic stress ( Yalin et al, 2007 ). Oxidative phosphorylation during anaerobic glycolysis lead to development of (ROS) .The cell in pancreases is unusually at risk for damage by pro-oxidant because it has low levels of antioxidant system .The family of GST genes have an active role in protecting cells from reactive oxygen speciese.GSTP1 causes the detoxification of products arising from oxidation of DNA (Yalin et al,2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, investigations have shown that the GSTM1 gene may play a significant role in the aetiopathogeneses of diabetes mellitus and could serve as a useful biomarker in the prediction of diabetes mellitus susceptibility of the Turkish population. [7] Poor glycemic control in diabetes and combination of oxidative, metabolic, and carbonyl stresses has been shown to cause restriction in supply but excessive demand for reducing equivalents. [61] Therefore, repressed NADH-MR activity in hyperglycemic rats could be linked to the substantial diversion and utilization of reducing equivalents to other reductive pathways in efforts to minimize oxidative stress, prompted by erythrocyte high ROS content.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes by virtue of their activities act as a subset of numerous cellular antioxidants defense systems against ROS species that are associated with many disease-causing electrophiles. [2,7,8] NADH-methaemoglobin reductase (NADH-MR) (EC: 1.6.2.2) transfers electrons from NADH + H + to cytochrome b 5 via its flavin adenine dinucleotide (FAD) prosthetic group. [9] This erythrocyte enzyme maintains hemoglobin in its ferrous (Fe 2+ ) state.…”
Section: Introductionmentioning
confidence: 99%